Surface Wave Tomography of the Alps Using Ambient‐Noise and Earthquake Phase Velocity Measurements. Issue 2 (28th February 2018) - Kästle, Emanuel D.; El‐Sharkawy, A.; Boschi, L.; Meier, T.; Rosenberg, C.; Bellahsen, N.; Cristiano, L.; Weidle, C.
Abstract: A large data set of surface wave phase velocity measurements is compiled to study the structures of the crust and upper mantle underneath the Alpine continental collision zone. Records from both ambient‐noise and earthquake‐based methods are combined to obtain a high‐resolution 3‐D model of seismic shear velocity. The applied techniques allow us to image the shallow crust and sedimentary basins with a lateral resolution of about 25 km. We find that complex lateral variations in Moho depth as mapped in our model are highly compatible with those obtained from receiver function studies; this agreement with entirely independent data is a strong indication of the reliability of our results, and we infer that our model has the potential to serve as reference crustal map of shear velocity in the Alpine region. Mantle structures show nearly vertical subducting lithospheric slabs of the European and Adriatic plates. Pronounced differences between the western, central, and eastern Alps provide indications of the respective geodynamic evolution: we propose that in the southwestern and northeastern Alps, the European slab has broken off. The complex anomaly pattern in the upper mantle may be explained by combination of remnant European slab and Adriatic subduction. Along‐strike changes in the upper mantle structure are observed beneath the Apennines with an attached Adriatic slab in the northern Apennines and a slab window in the central Apennines. There is also evidence for subduction of Adriatic lithosphere to the east beneath the Pannonian Basin and the Dinarides down to a maximum depth of about 150 km. Key Points: Different types of surface wave measurements are combined to create a 3‐D shear velocity model of the Alpine lithosphere The presented surface wave method allows to resolve subduction slabs in the uppermost mantle The model shows evidence for slab detachments under the western and eastern Alps